(untitled) (Interdisciplinary Studies Journal, 2025)
In this text, we draw on our pedagogical experience within the scope of Professional and Technological Education for Youth and Adults (EJA-EPT) with three classes composed exclusively of women to build a reflection on gender, work, and education. This experience took place in the Technical Secretariat course at IFSul, Venâncio Aires-RS campus, during the academic periods from 2019 to 2024. The discussion and analysis presented are based on reports from these EJA-EPT women students, in which we propose to listen to their experiences throughout the schooling process. The following question guides this work: what is the schooling trajectory of socially vulnerable women like? To this end, we address the specificities of this type of education and the socio-cultural aspects that shaped the path of these women students. This work is intertwined with a critical reflection on this professional experience and its impacts on building a more humane and humanizing teaching perspective. These experiences provided an opportunity to connect theoretical knowledge with professional teaching practice, consolidating a more critical view of the social roles traditionally assigned to women by patriarchal societies.